Using VO2max as a training-status marker? Is the question still valid in 2022? - Dotan, R. (Journal of Applied Physiology, 2023)
Podlogar et al.`s Viewpoint (1) and its associated Commentaries (2) raise issues deserving of commentary. A preliminary one concerns the surprising notion, expressed by some, that race-outcome prediction is central to laboratory testing. Not so! Field testing nearly always better simulates and more precisely predicts eventual race performance. However, merely knowing a runner to have covered 18 km in an hour of road running, cannot reveal the relative strengths/weaknesses of his/her fitness components, or which is more likely to benefit from additional training. The laboratory`s forte is in doing precisely that. The main issue, however, of whether maximal oxygen consumption (Vo2max) is an appropriate fitness/training-status marker, does not belong in a 2022 Viewpoint exchange but rather in the 1960s, when many still regarded Vo2max as the "holy grail" of fitness testing. Costill et al. (3) concluded, already in 1971, that "marathon running success may, to a large part, be determined by running economy, max Vo2, and the ability to utilize a large fraction of the max Vo2 during marathon competition." Running economy and Vo2max`s sustainable fraction ("pure endurance") are entirely independent of Vo2max. An illuminating example is Marathoner Derek Clayton, a 12-yr world-best-time holder (2:08:34 h), who had a lowly (among world-class runners) Vo2max of 69.7 mLO2·kg-1·min-1, but could sustain 86% of that throughout the race (4). Frank Shorter, the 1972 Olympic Marathon champion, was not much different.